INVESTMENT ANALYSIS OF SECTORS OF TRADE AND SERVICE, AND SUB-SECTORS OF TOURISM, HOTELS AND RESTAURANTS LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2011-2015 - Ichsani, Sakina; Susanti, Neneng (Universitas Brawijaya, Indonesia, 2017)
The tourism industry in Indonesia is increasingly developed. This is because governments are focusing and paying more attention to the tourism industry in Indonesia. Because of the bigger opportunity, it will be more company are keen to plunge into the world of tourism and take part in the tourism industry. The purpose of this study was to assess the feasibility of investment by using the technique of NPV and PI in trade, services and investment sub-sectors of tourism, hotels and restaurants listed on the Indonesian Stock Exchange in 2011-2015. From the research results can be seen that from the 19 companies listed on the Indonesian Stock Exchange, only six companies that are not worth the investment or not feasible, while 13 other companies eligible to invest. In generally in trade, services and investment sub- sectors of tourism, hotels and restaurants listed on the Indonesian Stock Exchange is feasible investment.